1998
DOI: 10.1111/j.1651-2227.1998.tb01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid shunt infections in infants and children in Mobile, Alabama

Abstract: Cerebrospinal fluid shunt systems are used to treat hydrocephalus in infants and children; unfortunately, some shunt systems become infected. We sought to define the epidemiology of shunt infections and shunt survival prior to infection at our institution. We identified 268 shunt procedures performed from January 1990 to June 1996 in 145 patients. There were 29 episodes of shunt infection for an incidence of 10.8% per procedure and 13.1% per patient. Staphylococcus epidermidis was the most common isolate recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…When examining the studies presented in evidence in Table 3 2,10,20,34 and Table 4, 8,9,[13][14][15]21,24,26,30,31 it is difficult to say with any degree of clinical certainty whether complete shunt removal leads to better shunt infection treatment outcomes than partial shunt removal. This is due, in part, to the paucity of outcome data comparing the 2 treatment options within the same study population, but also to the confounding effect of intrathecal antibiotic therapy, as described above.…”
Section: Arnell Et Al 2007mentioning
confidence: 99%
“…When examining the studies presented in evidence in Table 3 2,10,20,34 and Table 4, 8,9,[13][14][15]21,24,26,30,31 it is difficult to say with any degree of clinical certainty whether complete shunt removal leads to better shunt infection treatment outcomes than partial shunt removal. This is due, in part, to the paucity of outcome data comparing the 2 treatment options within the same study population, but also to the confounding effect of intrathecal antibiotic therapy, as described above.…”
Section: Arnell Et Al 2007mentioning
confidence: 99%
“…Current treatments carry high risk for additional complications (Blount et al, 1993;Bondurant and Jimenez, 1995;Patwardhan and Nanda, 2005) and neurological problems often persist after treatment (Fernell et al, 1994;Mancao et al, 1998;Del Bigio, 2004). Understanding the causes of hydrocephalus is critical for developing new treatment and prevention options.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a multitude of independent risk factors associated with shunt infection, including length of surgery, number of prior revisions, experience of the surgeon, etiology of hydrocephalus, patient age, immune status, and postoperative CSF leakage (1,10,12,18,19,27,28,30). Despite continued improvements in surgical and sterilization technique, perioperative antibiotic therapy, and appreciation of the aforementioned risk factors, significant reductions in infection rates remain elusive (10).…”
Section: Discussionmentioning
confidence: 97%